2017
DOI: 10.1515/esp-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electrospinning parameters and magnetic properties of BiFeO3 nanofibers

Abstract: BiFeO 3 nanofibers of different morphologies and dimensions were produced by electrospinning varying the collector and thermal treatment. By thermogravimetric analyses (TGA) the thermal behavior of the as-spun nanofibers was studied. The morphology of the nanofibers was examined by transmission and scanning electron microscopy (TEM and SEM, respectively) while the chemical composition and crystal structure were analyzed by energy dispersive x-ray spectrometry (EDS) and wide angle x-ray diffraction (WAXD). A vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Only 26% (weight) of BFO nanofibers remains after annealing, which is consistent with previous reports using similar synthesis protocols. 54,55 Based on this measurement, we can provide a fair estimate of the BFO nanofibers weight of 0.6, 1.2, 2.4, 3.6, and 6.0 mg for samples obtained after 0.5, 1, 2, 3, and 5 min, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Only 26% (weight) of BFO nanofibers remains after annealing, which is consistent with previous reports using similar synthesis protocols. 54,55 Based on this measurement, we can provide a fair estimate of the BFO nanofibers weight of 0.6, 1.2, 2.4, 3.6, and 6.0 mg for samples obtained after 0.5, 1, 2, 3, and 5 min, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, R. E. S. Bretas et al demonstrated that the magnetic properties (i.e. saturation magnetization) of BiFeO3 nanofibers produced by electrospinning increased with the decrease of the nanofibers' diameter and increase of nanofibers interconnectivity [146].…”
Section: 332mentioning
confidence: 99%